Coastal Ocean Darkening Effects via Terrigenous DOM Addition on Plankton: An Indoor Mesocosm Experiment - Mustaffa, Nur Ili Hamizah; Kallajoki, Liisa; Biederbick, Johanna; Binder, Franziska Isabell; Schlenker, Alexandra; Striebel, Maren (Frontiers in Marine Science, 2020)
Human activities, increasing precipitation, and changes in land run-off deliver a large input of allochthonous nutrients into coastal waters including terrigenous dissolved organic matter (tDOM). Increased subsidies of tDOM into the coastal water are expected to reduce light availability and thus might be one of the factors causing coastal ocean darkening. To investigate the effect of increased tDOM input and thus limitation in light availability on primary production as well as the transfer to higher trophic levels (zooplankton), we conducted a large-scale indoor mesocosm “Planktotrons” experiment with natural (pelagic and benthic) plankton communities from the North Sea. We simulated a coastal ocean system with daily light and tidal cycles for 35 days. The experimental treatments included a light gradient consisting of three levels of tDOM addition (i.e., low tDOM, medium tDOM and high tDOM) and a control without tDOM addition. Results showed that tDOM addition reduced the light availability by 27% (low tDOM addition), 62% (medium tDOM addition) and 86% (high tDOM addition). Light reduction through tDOM addition negatively influenced phytoplankton biomass during the first half of the experiment (< 18 days) mainly in the ‘medium tDOM’ and ‘high tDOM’ treatments. The tDOM addition changed the phytoplankton community composition, potentially due to adaptations to different light conditions. Neither phytobenthos biomass nor composition was significantly affected by tDOM addition, probably because the tidal cycle assured sufficient light availability during low tide. Overall, our results indicate that the tDOM addition negatively influenced phytoplankton biomass and composition via light availability and tDOM effects were also observed on the zooplankton level (biomass and C:N ratio). Our experiment demonstrates possible implications of coastal darkening under climate-driven environmental changes on primary producers and their interactions in the aquatic food web.